New player in CAR-T manufacture field: comparison of umbilical cord to peripheral blood strategies - Rassek, Karolina; Misiak, Jan; Ołdak, Tomasz; Rozwadowska, Natalia; Basak, Grzegorz; Kolanowski, Tomasz (Frontiers in Immunology, 2025)
One of the most successful treatments in hematologic cancer is chimeric antigen receptor (CAR)-T cell-based immunotherapy. However, CAR-T therapy is not without challenges like the costly manufacturing process required to personalize each treatment for individual patients or graft-versus-host disease. Umbilical cord blood (UCB) has been most commonly used for hematopoietic cell transplant as it offers several advantages, including its rich source of hematopoietic stem cells, lower risk of graft-versus-host disease, and easier matching for recipients due to less stringent HLA requirements compared to bone marrow or peripheral blood stem cells. In this review, we have discussed the advantages and disadvantages of different CAR-T cell manufacturing strategies with the use of allogeneic and autologous peripheral blood cells. We compare them to the UCB approach and discuss ongoing pre-clinical and clinical trials in the field. Finally, we propose a cord blood bank as a readily available source of CAR-T cells.